2003
DOI: 10.1021/ja0377551
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of the Cycloaddition of Thiobenzophenone S-Methylide to Thiobenzophenone

Abstract: The cycloaddition of thiobenzophenone S-methylide to thiobenzophenone, an experimentally well-known reaction, was studied, using (U)HF/3-21G* for finding stationary points and (U)B3LYP/6-31G*//(U)HF/3-21G* single-point calculations for energies. Some optimizations were performed by (U)B3LYP/ 6-31G* to check the reliability of the calculations. The comparison of the concerted pathways and stepwise reactions via C,C-biradicals and C,S-zwitterions showed that the formation of a tetraphenyl-substituted C,C-biradic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…Depending on the basis set, the values range from 16 to 34 %. As observed in other examples, [26] such low BRCs also yield closed-shell wave functions (S 2 = 0) when determined by unrestricted Figure 2. Volume profile [a] of the reaction between 1,4-cyclohexadiene (3) and DDQ (1 a).…”
supporting
confidence: 81%
“…Depending on the basis set, the values range from 16 to 34 %. As observed in other examples, [26] such low BRCs also yield closed-shell wave functions (S 2 = 0) when determined by unrestricted Figure 2. Volume profile [a] of the reaction between 1,4-cyclohexadiene (3) and DDQ (1 a).…”
supporting
confidence: 81%
“…7). A DFT study showed that this result is best explained by formation of a biradical intermediate, which closes to the 4,5-substituted 1,3-dithiolane [93]. A combined experimental and theoretical study on cycloadditions of aliphatic thiocarbonyl S-ylides to thiobenzophenone, where synchronous and two-step pathways compete, showed good agreement between experiment and theory [94].…”
Section: Scheme 24mentioning
confidence: 74%
“…Whereas, in the case of 5a 4 in the absence of trapping agents yielded 9 as the sole product. This reaction corresponds with the formation of analogous products from thioketones and α-diazo carbonyl derivatives [8].…”
Section: Methodsmentioning
confidence: 90%
“…Among the few methods of their generation, the reaction of CH 2 N 2 with C=S dipolarophiles and subsequent elimination of N 2 is applied most frequently. The reactive 1,3-dipoles formed in situ can be trapped by different electron-deficient dipolarophiles, but aromatic thioketones proved to be the most reactive ones (superdipolarophiles [4]). Less reactive C=S dipolarophiles are non-enolizable aliphatic thioketones, 1,3-thiazole-5(4H)-thiones, dithioesters, and O-alkyl thioesters.…”
mentioning
confidence: 99%